The art of body talk : how to decode gestures, mannerisms, and other non-verbal messages - Hartley, Gregory; Karinch, Maryann (Career Press, 2017)
The Art of Body Talk gives you the fastest, most efficient method to read anyone's body language. You will easily be able to perceive the emotions and spot the messages people are really sending--whether they know it or not (and whether they want to or not!).